Molecular biology of cell nonpermissiveness to retroviruses. Has the time come? - Svoboda, J (Gene, 1998)
The problem of host cell nonpermissiveness to retrovirus infection is characterized and illustrated on several retroviral models, including the role of viral receptors, cell fusion, and endogenous retroviral genomes as modifiers of the outcome of retroviral infection. Special attention is paid to different barriers against the infection of mammalian cells with avian leukosis/sarcoma viruses (ALV/ASV). Even when avian retroviruses become integrated in mammalian cells, several blocks at the level of provirus expression, processing of viral RNAs, and posttranslational modification prevent virus production in such virogenic cells. The significance of these blocks and new strategies making it possible to overcome some of them are discussed in relation to the development of ALV/ASV-based vectors suitable for gene therapy in mammals.
Keywords: replikace viru; Retroviridae Infections; zvířata; Humans; Retroviridae; Virus Replication; retrovirové infekce; lidé; Animals